Political budget cycles: Evidence from Italian cities. (26th April 2017) - Alesina, Alberto; Paradisi, Matteo
Abstract: The introduction of a new real estate taxes in Italy in 2011 provides a natural experiment, which is useful to test for political budget cycles. The new real estate tax allowed discretion to local governments. This generates a random variation in the distance of municipalities from the following elections when they choose the level of the tax rate. We do find substantial evidence of political budget cycles, with municipalities choosing lower tax rates when close to elections. We observe this budget cycle for smaller municipalities where the tax was more likely to be the single most important issue for the local government. Cities close to elections with large deficits did not set lower rates and so did municipalities with a lower average value of properties. Finally, the political budget cycle is stronger in the South.